Potential neural substrates underlying circadian and olfactory disruptions in preclinical Alzheimer’s disease - Quiana L. Jeffs; Jonathan F. Prather; William D. Todd (Frontiers in Neuroscience, 2023)
Alzheimer’s disease (AD) is the leading cause of dementia, with over 45 million patients worldwide, and poses significant economic and emotional burdens to both patients and caregivers, significantly raising the number of those affected. Unfortunately, much of the existing research on the disease only addresses a small subset of associated symptomologies and pathologies. In this review, we propose to target the earliest stages of the disease, when symptomology first arises. In these stages, before the onset of hallmark symptoms of AD such as cognitive impairments and memory loss, circadian and olfactory disruptions arise and are detectable. Functional similarities between circadian and olfactory systems provide a basis upon which to seek out common mechanisms in AD which may target them early on in the disease. Existing studies of interactions between these systems, while intriguing, leave open the question of the neural substrates underlying them. Potential substrates for such interactions are proposed in this review, such as indirect projections that may functionally connect the two systems and dopaminergic signaling. These substrates may have significant implications for mechanisms underlying disruptions to circadian and olfactory function in early stages of AD. In this review, we propose early detection of AD using a combination of circadian and olfactory deficits and subsequent early treatment of these deficits may provide profound benefits to both patients and caregivers. Additionally, we suggest that targeting research toward the intersection of these two systems in AD could uncover mechanisms underlying the broader set of symptoms and pathologies that currently elude researchers.